Teacher alienation in Hong Kong. Issue 3 (4th May 2018) - Tsang, Kwok Kuen
ABSTRACT: Teachers' negative emotions began to receive attention in the Hong Kong context in the mid-1990s. As negative emotions may affect both teachers' well-being and the quality of their teaching, Hong Kong education policy-makers and educators have used psychological approaches to determine the reasons why teachers experience negative feelings. However, these approaches fail to accommodate the social causes of negative emotions. Therefore, this study investigates the possible social causes of teachers' negative emotions from the perspective of alienation theory. In-depth interviews with 21 teachers in Hong Kong reveal that Hong Kong teachers may be suffering from alienation (characterised by a sense of powerlessness, meaninglessness, isolation, and self-estrangement) due to their experiences of teaching, their employment status, and their structural position in schools, which are related to the occupational and organisational structure of teaching. The findings also indicate that patterns of alienation may differ between more and less experienced teachers.